Monitoring with social media: Experiences from “integrating” WhatsApp in the M&E system under sweet potato value chain - Chesoli, R.N.; Mutiso, J.M.; Wamalwa, M. (Walter de Gruyter GmbH, 2020)
Dealing with multiple stakeholders in agriculture–nutrition projects often makes communication and the collection of quality, reliable, and low-cost data complex and challenging. Communication bureaucracies among stakeholders often lead to delay, distortion, or loss of information along the communication channel. Social networking platforms can facilitate communication and collection of real-time data useful for project monitoring. This article shares our experience in using the WhatsApp platform for communication and collection of additional monitoring data. A WhatsApp platform for project implementers from the ministries of health (100) and agriculture (52) from Bungoma, Busia, Homa Bay, and Migori counties Kenya was formed in September 2016 for sharing additional monitoring data in the form of photos, videos, and texts. Project monitoring-related costs reduced by 51% and collapsing reporting hierarchies reduced information delays, thereby saving time and communication challenges. A shared understanding among different actors on the project’s indicators, reporting timelines, and data collection guidelines improved the quality of continuous monitoring data. However, staff transfer and replacements called for the continuous induction of new entrants to the forum. WhatsApp is a compelling tool in project monitoring to mitigate communication challenges. It offers an opportunity to share information on one platform among different cadres, facilitating collective action in multisectoral approach projects.